Hypnerotomachia Poliphili: Thoughts on the Earliest Reception .......... 231 - Caruso, Carlo; Russell, James (Tra l’antica sapientia e l’imaginatio: Nuovi studi sul Polifilo, 2020)
The earliest reception of Francesco Colonna’s Hypnerotomachia Poliphili is here examined with the intent of casting some light on its author’s aims and purposes through the opinions of contemporary readers. In this respect annotated copies, and the one preserved at the Biblioteca Comunale degli Intronati in Siena in particular (the importance of which was first highlighted by Edoardo Fumagalli), can offer relevant exegetic material. Another aspect considered here is the significance of the work’s language, a unique variety of Italian vernacular heavily mixed with Latin and Greek. In line with what transpires from the comments of its Renaissance readers, Colonna’s fantastic as well as erudite language may be regarded as a deliberate experiment aiming to mimic the earliest vernacular language as it emerged after the dissolution of Latin. The work’s linguistic experimentalism should thus be inscribed within the fifteenth- and early sixteenth-century debate on the origin of the vernacular.